Effect of Polymers on the Micellization of Surfactants by Conductance Measurements - Singh, R.P.; Tomer, A.S.; Chaudhary, Romy (Asian Journal of Chemistry, 2010)
The micellization behaviour of anionic and cationic surfactants in the presence of charged (human serum albumin and ribonucleic acid) and neutral polyvinyl pyrrolidone polymers was investigated by means of conductance measurements. The plots of conductance vs. concentraton of surfactants exhibited sharp inflexion at critical micelle concentration (CMC). The conductance was found to increase with the progressive addition of the respective polymers, however the extent of increase was comparatively more in the premiceller than in the postmiceller regions as the polymer formed mixed micelles. The rise in conductance of surfactants-polymer mixt-ures was ascribed to the alteration in the nature of solvent as the polymer formed mixed micelles with the surfactants by the incorportion of the polar part of polymers in the micelles. Ribonucleic acid was found to increase the CMC of cationic surfactants while those for anionic, it was decrases. On the other hand, human serum albumin and polyvinyl pyrrolidone caused a decrease in CMC of both cationic and anionic surfactants. The mechanism has been suggested through electrostatic, hydrophobic and cooperative types of linkage between surfactants and the polymers.